Using an Improvised Abacus to Assist Samproso M/A Junior High School Level One Pupils to Overcome the Problem of Place Value Concept in Mathematics - Amoah, Daniel; B. Bour, Kwame; Boampong , Samuel; Arkoh , Bright (International Journal of Scientific Research and Management (IJSRM), 2019)
This study is an action research work done to help the JHS one (1) pupils of Samproso M/A Basic School in Offinso South Municipal Assembly to identify place value of 4 - 5 digits in numerals. The study was undertaken in order to bring out the meaning of place value, the importance of teaching and learning materials (TLMs) in teaching and also the teaching and learning materials (TLMs) that could be used in teaching place value as a concept in mathematics. The study used an improvised abacus to help improve pupils’ understanding of the concept of place value. Purposive as well as random sampling technique was selected and used as the study was limited to where the problem was identified and they all shared the same problem. In all, sixty-five (65) pupils comprising thirty-three (33) boys and thirty-two girls from the sample groups were used. Three research questions were formulated to guide the study. Pre-test, observation, interview questionnaire and post-test were the research instruments used to gather reliable data for the study. Pupils were also found to have developed favourable attitude towards mathematics. Recommendations were made with regards to teachers and pupils’ attitude in the teaching of mathematics at the basic school level